Ustaz Yahya Othman murabbi sepanjang zaman - Mohd. Nazeli Ahmad Arifin (ILHAM Centre, 2014)
Biography of Yahya Othman, a politician and religious mentor to the members of Islamic Party of Malaysia from Kelantan